Assalamualaikum Bejing Repackaged: Habitus, Symbolic Power and Indonesian Cultural Production - Adji, Alberta Natasia (UI Scholars Hub, 2019)
This article explores the adaptation of Asma Nadia’s Assalamualaikum Beijing from novel to film to comic book as the reproduction of symbolic cultural goods. According to Bourdieu’s concept of habitus, people are conditioned to perform repetitive acts devoid of any preceeding consideration or deliberation, while symbolic power represents the tacit modes of social/cultural domination ingrained and preserved through everyday social practices. Taking a sociology of literature approach, this study discovers that the habitus of the Indonesian canon literary tradition has hindered contemporary literary works from achieving the same level of legitimacy through the boundary work performed by literary awards. Contemporary pop authors, who rarely win these awards, have set up a new standard through which they can gain influential status over the Indonesian field of cultural production through the repeated “repackaging” of their literary works. In addition, the study finds that Asma Nadia’s use of Beijing as the setting for her work is represents her desire to introduce the existence of Islam in China, while implicitly hinting at “a solution” to the problematic existence of Chinese Indonesians who can only be “fixed” through religious conversion.